2018
DOI: 10.18488/journal.aefr.2018.88.1111.1125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance Mechanisms on Bank Performance Evidence from Saudi Banking Sector

Abstract: Corporate governance mechanisms Bank performance Saudi banking sector ROA ROE Board independence Ownership of the largest Shareholder Foreign ownership Audit committee size.This study investigates the effect of Corporate Governance Mechanisms on bank performance, using a sample of nine Saudi banks during the period 2011-2016. The study employed six corporate governance mechanisms to examine their effect on two performance measures; ROA and ROE. In addition, the study used three control variables to separate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
4
20
0
3
Order By: Relevance
“…As seen in Model 1, the relationship between GDP and ROA and the exchange rate and ROA are positively significant at (P < 0.01), while the relationship between ROA and the other control variables such as inflation, non-performing loans, and bank deposits are negatively significant. These results are consistent with previous literature on the relationship of these macroe-economic variables and banking sector profitability (Al-Homaidi et al, 2019;AlSagr et al, 2018;Belkhaoui et al, 2020;Bhattarai, 2018;El-Chaarani, 2019;Zampara et al, 2017). In Model 2, we add GPR and oil rents to the control variables presented in Model 1.…”
Section: Emperical Estimationsupporting
confidence: 89%
“…As seen in Model 1, the relationship between GDP and ROA and the exchange rate and ROA are positively significant at (P < 0.01), while the relationship between ROA and the other control variables such as inflation, non-performing loans, and bank deposits are negatively significant. These results are consistent with previous literature on the relationship of these macroe-economic variables and banking sector profitability (Al-Homaidi et al, 2019;AlSagr et al, 2018;Belkhaoui et al, 2020;Bhattarai, 2018;El-Chaarani, 2019;Zampara et al, 2017). In Model 2, we add GPR and oil rents to the control variables presented in Model 1.…”
Section: Emperical Estimationsupporting
confidence: 89%
“…Similarly, Chughtai and Tahir (2015), Faisal et al (2016) examined the IBs in Pakistan and Grove et al (2011), Wang et al (2012) in the USA, Farag and Mallin (2017) in Europe, Sakawa and Watanabel (2018) in Japan, Chazi et al (2018) in the GCC and Wasiuzzaman and Nair Gunasegavan (2013) in Malaysia, found that CG significantly affects the profitability of IBs. In light of past researches on IBs, some authors (AlSagr et al , 2018; Aslam et al , 2018; Bahreini and Zain, 2013; Farag et al , 2018; Grassa and Matoussi, 2014a; Mollah et al , 2017; Nawaz, 2019) have identified several essential CG mechanisms, and these include board size (BS), non-executive directors, CEO duality, audit committees and Shariah committee. Therefore, this investigation used the viability of these mechanisms as an intermediary to quantify the CG quality of IBs.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, CG is widely accepted as a significant determinant to enhance banks’ performance (Aktan et al , 2018; Aslam et al , 2019a, 2019b). Therefore, banks with prudent CG structure are perceived to be more efficient in allocating the bank resources to generate more profit (AlSagr et al , 2018; Hussien et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Audit committee is a standing committee of governance that is established to enhance the financial accountability, unwavering quality, and transparency in organisations, whereby the auditor and the management strengthen the financial reporting in the organizations according to the general accounting and legal standards (AlSagr et al, 2018). It also serves as a scaffold in the correspondence network among auditors and board of directors as well as enable them to adequately check the power of the board with specific reference to the accounting standards (Rehman et al, 2021).…”
Section: B4 Audit Committeementioning
confidence: 99%